Knowledge regarding oral rehydration solution among mothers of under five children from a rural area of Rangareddy district, Telangana - Ghatam, Anjaneyulu; Maktha, Vijay Kumar; Katiki, Sreenadh Venkata; Koka, Bhargavi (International Journal Of Community Medicine And Public Health, 2017)
Background: Diarrhea is still a major killer of children under five. Almost all the deaths due to diarrhoea can be averted by preventing and treating dehydration by use of ORS (oral rehydration solution). Methods: A cross sectional study was done among mothers who had children of 6 months to 5 years of age. Study area was rural health and training centre (RHTC), Peddamangalaram, Department of Community Medicine, Bhaskar Medical College, Rangareddy District, Telangana. 100 mothers were selected for the study by convenient sampling technique. A pre designed, pre tested questionnaire was used to get the relevant information. Results: Mean age of the mothers was 24.87±5.8 years with majority belonged to Hindu religion, one fourth were illiterates and two thirds were home makers. About two thirds (62%) were aware about the oral rehydration solution, but only 58% agreed that ORS is useful and only 54% knew the condition where ORS is used. Health workers (ASHA/ANM) were the major sources of information about ORS. Conclusions: The present study thus corroborates to that of observations made by various authors; denoting there is a gap between knowledge and practice of administering ORS in diarrhoeal diseases in children.